2016
DOI: 10.2298/tsci141225077m
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of convective heat transfer enhancement using alumina/water and copper oxide/water nanofluids

Abstract: The nanofluids are widely used for heat transfer applications in the various engineering applications. The nanoparticles dispersed uniformly in the base fluid on proper mixing. In the present study, Al 2 O 3 and CuO nanoparticles were selected and the changes in the heat transfer coefficient were investigated in the complete laminar and discrete points of transition fluid flow through a copper tube with constant heat flux. The heat transfer coefficient was investigated at different loading of Al 2 O 3 and CuO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
4
11
0
Order By: Relevance
“…As shown in Figure 8b, results achieved by Jumpholkul et al [143] show very good agreement with the research of Martinez-Cuenca et al [137]. [82,87,137,143] As shown in Figure 9, for Re < 1700, average HTC obtained by Mangrulkar et al [132] is clearly lower than in the study by Minakov et al [118]. However, for Re > 1700, the results of Mangrulkar et al [132] follow the same trend as the data of Minakov et al [118].…”
Section: Water-tio2 Nanofluidssupporting
confidence: 84%
See 2 more Smart Citations
“…As shown in Figure 8b, results achieved by Jumpholkul et al [143] show very good agreement with the research of Martinez-Cuenca et al [137]. [82,87,137,143] As shown in Figure 9, for Re < 1700, average HTC obtained by Mangrulkar et al [132] is clearly lower than in the study by Minakov et al [118]. However, for Re > 1700, the results of Mangrulkar et al [132] follow the same trend as the data of Minakov et al [118].…”
Section: Water-tio2 Nanofluidssupporting
confidence: 84%
“…Figure 1a shows the average HTC as a function of the Re number. As shown in Figure 1a, the agreement between the results of Shokouhi et al [76] and Mangrulkar et al [132] is very good, even though different thermal boundary conditions were used-see Table 1. Figure 1b shows the dependence of the local HTC as a function of the Re number for the closest possible dimensionless distance from the inlet.…”
Section: Ceramic Nanofluidssupporting
confidence: 59%
See 1 more Smart Citation
“…14. The experimental data in all cases were lower than those computed number from the correlation of Petukhov, with a deviation between 12.4% and 17.6% and an average of the deviation of 14 In another study, Mangrulkar et al [36] evaluated the convective heat transfer performances of Al 2 O 3 -water and CuO-water nanofluids within a horizontal copper tube for a wide range of volumetric concentrations (0.1 -0.5%) and Reynolds number (500-3000). It was found that both nanofluids exhibited better heat transfer characteristics compared to pure water in laminar and transitional flow regimes.…”
Section: Numentioning
confidence: 63%
“…Industry and research teams usually identify several parameters that can affect descaling performance, including several angles and nozzle distances [6] or nanoparticles presented in water [7,8]. Even the structure of the oxidized surface plays important role in the process [9].…”
Section: Introductionmentioning
confidence: 99%